2010
DOI: 10.1016/j.cvfa.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Coronavirus Associated Syndromes

Abstract: Bovine coronaviruses, like other animal coronaviruses, have a predilection for intestinal and respiratory tracts. The viruses responsible for enteric and respiratory symptoms are closely related antigenically and genetically. Only 4 bovine coronavirus isolates have been completely sequenced and thus, the information about the genetics of the virus is still limited. This article reviews the clinical syndromes associated with bovine coronavirus, including pneumonia in calves and adult cattle, calf diarrhea, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
199
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(210 citation statements)
references
References 90 publications
7
199
1
3
Order By: Relevance
“…The bovine coronavirus (BCoV) is a global pathogen that is recognized as the causative agent of enteric disease; however, the contribution of this pathogen towards the development of bovine respiratory disease (BRD) was underestimated compared to those of viruses that are primary agents of BRD, such as the bovine herpesvirus 1, bovine viral diarrhea virus, bovine parainfluenza-3 virus, and bovine respiratory syncytial virus (Fulton et al, 2011). However, recent reports have indicated that BCoV might also be a major pathogen of BRD (Lathrop et al, 2000;Boileau and Kapil, 2010;Hick et al, 2012). Moreover, isolates of BCoV associated with neonatal and adult diarrhea are referred to as BECoV (bovine enteric or enteropathogenic coronaviruses), whereas strains isolated from nasal secretions and lung of cattle affected by pneumonia have been classified as bovine respiratory coronaviruses, BRCoV (Lin et al, 2000;Boileau and Kapil, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bovine coronavirus (BCoV) is a global pathogen that is recognized as the causative agent of enteric disease; however, the contribution of this pathogen towards the development of bovine respiratory disease (BRD) was underestimated compared to those of viruses that are primary agents of BRD, such as the bovine herpesvirus 1, bovine viral diarrhea virus, bovine parainfluenza-3 virus, and bovine respiratory syncytial virus (Fulton et al, 2011). However, recent reports have indicated that BCoV might also be a major pathogen of BRD (Lathrop et al, 2000;Boileau and Kapil, 2010;Hick et al, 2012). Moreover, isolates of BCoV associated with neonatal and adult diarrhea are referred to as BECoV (bovine enteric or enteropathogenic coronaviruses), whereas strains isolated from nasal secretions and lung of cattle affected by pneumonia have been classified as bovine respiratory coronaviruses, BRCoV (Lin et al, 2000;Boileau and Kapil, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent reports have indicated that BCoV might also be a major pathogen of BRD (Lathrop et al, 2000;Boileau and Kapil, 2010;Hick et al, 2012). Moreover, isolates of BCoV associated with neonatal and adult diarrhea are referred to as BECoV (bovine enteric or enteropathogenic coronaviruses), whereas strains isolated from nasal secretions and lung of cattle affected by pneumonia have been classified as bovine respiratory coronaviruses, BRCoV (Lin et al, 2000;Boileau and Kapil, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Coronaviruses also cause a spectrum of diseases in farm animals and domesticated pets, some of which can be dangerous and are a risk to the farming industry (8)(9)(10)(11)(12). Only 4 bovine coronavirus isolates have been fully sequenced and, hence, the knowledge about the genetics of the virus is still insufficient (13). Reports (2,(14)(15)(16) indicate that the coronavirus is an important cause of diarrhea in calves accounting for between 4% and 26% of isolates, although it is also associated with healthy calves (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Betacoronavirus 1 (BCoV-1; order Nidovirales, family Coronaviridae, subfamily Coronavirinae, genus Betacoronavirus) is one of the important agents of neonatal calf diseases 1 and has become a worldwide infectious agent in the cattle industry. 1,3 First identified as a diarrheic agent in calves in 1973 in the United States, 10 BCoV-1 can cause diarrhea in calves, 2 winter dysentry 6 in adult cattle, and respiratory system infections in various aged cattle, 8,14 resulting in serious economic losses.…”
mentioning
confidence: 99%
“…1,3 First identified as a diarrheic agent in calves in 1973 in the United States, 10 BCoV-1 can cause diarrhea in calves, 2 winter dysentry 6 in adult cattle, and respiratory system infections in various aged cattle, 8,14 resulting in serious economic losses.…”
mentioning
confidence: 99%